Humor and Fear-Two Sides of the Same Coin?: Experimental Evidence on Humor Appeals in Health Communication Related to Childhood Vaccination - Florian Fischer; Florian Fischer; Franziska Carow; Stefanie Gillitzer (Frontiers Media S.A., 2021)
Until now, health communication has largely failed to debunk fears and caveats related to vaccination. This study aims to investigate the effects of different text types used in health communication in an experimental study design. A neutrally formulated text was compared to a humorous text using the formula of a fairytale. Overall, the study indicates no additional value in using the humorous format as an innovative and target-group-oriented approach to inform readers about scientific evidence related to vaccination. Although the effects of the two text types do not differ, the credibility of the neutrally formulated text was much more likely to be judged as high. This indicates that the perception of credibility is not the only criterion in health communication leading to knowledge gains and changes in health-related attitudes and behaviors.